Consider e raised to the RHS
e^{i(x/2) + ln[2cos(x/2)]}
= e^ix/2 * 2cos(x/2)
= 2cos(x/2) * [cos(x/2) + i*sin(x/2)]
= 2cos^2 (x/2) + i*sin(x)
= (cosx + 1) + i*sinx
= 1 + cosx+isinx
= 1 + e^ix
= e raised to LHS
2007-06-19 18:30:34
·
answer #1
·
answered by Dr D 7
·
1⤊
0⤋
Prove the identity ln[1 + e^(ix)] = i(x/2) + ln[2cos(x/2)].
Remember the trig identities.
e^(ix) = cos x + i sin x
cos x = 2cos²(x/2) - 1
sin x = 2sin(x/2) cos(x/2)
____________
Let's start with the left hand side.
Left Hand Side = ln[1 + e^(ix)] = ln[1 + cos x + i sin x]
= ln{1 + (2cos²(x/2) - 1) + i[2sin(x/2) cos(x/2)]}
= ln{2cos²(x/2) + 2i sin(x/2) cos(x/2)}
= ln{2cos(x/2)[cos(x/2) + i sin(x/2)]}
= ln{2cos(x/2)[e^(ix/2)]} = ln[2cos(x/2)] + ln[e^(ix/2)]
= ln[e^(ix/2)] + ln[2cos(x/2)]
= i(x/2) + ln[2cos(x/2)] = Right Hand Side
2007-06-20 02:17:50
·
answer #2
·
answered by Northstar 7
·
0⤊
0⤋
we have the identity
e^ix= cos x + i sin x
so ln(1 + e^ix)
= ln(1+cos x + i sin x)
= ln[2cos^2 (x/2) +i 2sin (x/2) cos (x/2) ----------------[using the identities cos 2x=2cos^2 x -1 ,and sin 2x=2sin x cos x]
=ln[2cos (x/2) {cos (x/2) + i sin (x/2)}
=ln[2cos (x/2)] + ln[e^(i x/2)]
=ln[2cos (x/2) + i x/2 ---------------[since ln (e^x)=x]
= i(x/2) + ln[2cos (x/2)]
2007-06-20 01:40:56
·
answer #3
·
answered by Sparrow G 2
·
0⤊
0⤋
ln(1+e^ix) - ln[2cos(x/2)] = ln[(1+e^ix) / (2cos(x/2)) ]
= ln[(1+e^ix) / (e^i(x/2)+e^-i(x/2)) ]
= ln[e^i(x/2)(e^i(x/2)+e^i(-x/2)) / (e^i(x/2)+e^i(-x/2)) ]
= ln[e^i(x/2)]
= i(x/2)
2007-06-20 01:35:24
·
answer #4
·
answered by nicolas_aquelet 2
·
0⤊
0⤋
1=e^(ix/2)e^(-ix/2);
hence
1+e^(ix)
=e^(ix/2)(e^(-ix/2)+e^(ix/2))
=e^(ix/2)(2cos(x/2));
hence take logarithm on both sides, we have desired results. The last step because e^(ix)=cos(x)+isin(x).
2007-06-20 01:37:06
·
answer #5
·
answered by yanglim2001 1
·
0⤊
0⤋
oh man.....sorry i cant help
2007-06-20 01:29:43
·
answer #6
·
answered by yah 3
·
0⤊
1⤋